Respiratory muscle strength and aerobic performance of wheelchair basketball players - Raphael N. Pereira; Marcos Fabio R. Abreu; Camila B. Gonçalves; Wilson Flávio S. Corrêa; Daniel R. Mizuhira; Marlene A. Moreno
Abstract The respiratory system has been described as a limiting factor in the performance of athletes. Therefore, the objective of this study was to evaluate the relationship between the respiratory muscle strength (RMS) and aerobic performance of wheelchair basketball players (WCBPs). We evaluated 19 male WCBPs who were divided into two groups: trunk control group (TCG) and without trunk control group (WTCG). All participants underwent a pulmonary function test, evaluation of maximal inspiratory (MIP) and expiratory (MEP) pressures, and an aerobic performance test. The MIP of both groups and the MEP values of TCG exceeded the predicted values for age and gender. No differences were observed in the MIP and aerobic performance between the groups although a difference was observed in the MEP values. Positive correlations were observed between MIP/MEP and the aerobic performance for both groups. These results suggested that the overall RMS of this group of WCBPs fell within or above the predicted values. Hence, the study concluded that RMS can positively influence the aerobic performance of WCBP.